2002
DOI: 10.4049/jimmunol.169.2.888
|View full text |Cite
|
Sign up to set email alerts
|

The Primary Antibody Repertoire Represents a Linked Network of Degenerate Antigen Specificities

Abstract: In this study, germline Abs were used to select clones from a random dodecapeptide phage-display library. This revealed a much greater heterogeneity of binders than could be obtained with mutated daughter Abs that presumably had been selected in vivo by nominal Ag during active immune responses. We demonstrate that the pluripotency of germline Abs can subsequently be optimized by binding interactions that correlate with thermodynamic changes indicative of structural adaptations at the interface. This singular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
80
0
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 80 publications
(89 citation statements)
references
References 51 publications
(48 reference statements)
5
80
0
2
Order By: Relevance
“…Peptides were essentially derived using the Phage Display Peptide Library Kit (New England Biolabs, Cambridge, MA), as previously reported (6). Interactions between Ab and peptide and their thermodynamic analysis by surface plasmon resonance have also been previously reported (6).…”
Section: Peptidesmentioning
confidence: 99%
See 2 more Smart Citations
“…Peptides were essentially derived using the Phage Display Peptide Library Kit (New England Biolabs, Cambridge, MA), as previously reported (6). Interactions between Ab and peptide and their thermodynamic analysis by surface plasmon resonance have also been previously reported (6).…”
Section: Peptidesmentioning
confidence: 99%
“…It was suggested that a degree of polyreactivity within a germline Ab would provide a way by which a single Ab would be able to recognize a range of Ags and so obviate the requirement for a singular Ab for every potential non-self immunogen (5)(6)(7)(8)(9). Even the mutation-driven modulations of epitopes could be handled very efficiently by primary humoral immune defense through use of such polyreactive Abs (10).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Cependant, la diversité dérivant uniquement de ces mécanismes est limitée et ne permet pas de faire face à l'hétérogénéité, théoriquement infinie, des antigènes potentiels présents dans la nature ou générés de manière synthé-tique. Cette limitation est compensée par la dégénérescence de la spécificité de certains récepteurs immunitaires, qui peut être considérée comme un deuxième niveau de diversification du réper-toire immunitaire [3,4]. Ainsi, certaines immunoglobulines (Ig) membranaires et solubles sont capables de s'adapter à de nombreux antigènes structurellement différents.…”
Section: Mécanismes De Diversification Du Répertoire Immunitaireunclassified
“…Ces immunoglobulines sont dites polyréactives [4]. Un grand nombre de travaux suggèrent que la capacité des anticorps polyréactifs à se lier à de multiples déterminants antigéniques est due à la plasticité conformationnelle de leurs domaines de liaison à l'antigène, qui leur permet de s'adapter à de nombreuses structures et séquences antigéniques différentes [3,4]. Dès lors, un répertoire normal d'immunoglobulines possède un continuum de réactivités antigéniques, allant d'une spécificité antigénique très restreinte (monoréac-tivité), à la capacité de reconnaître des antigènes structurellement différents (polyréactivité) [4].…”
Section: Mécanismes De Diversification Du Répertoire Immunitaireunclassified